In vivo studies of analgesic, antidiabetic, and CNS depressant properties of Pterocarpus indicus leaf extract - Tabassum, Farzana (Brac University, 2024)
A thesis submitted to the School of Pharmacy in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.